2012
DOI: 10.1038/nature11433
|View full text |Cite
|
Sign up to set email alerts
|

Codon-usage-based inhibition of HIV protein synthesis by human schlafen 11

Abstract: In mammals, one of the most pronounced consequences of viral infection is the induction of type I interferons, cytokines with potent antiviral activity. Schlafen (Slfn) genes are a subset of interferon-stimulated early response genes (ISGs) that are also induced directly by pathogens via the interferon regulatory factor 3 (IRF3) pathway1. However, many ISGs are of unknown or incompletely understood function. Here we show that human SLFN11 potently and specifically abrogates the production of retroviruses such … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
375
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 318 publications
(412 citation statements)
references
References 28 publications
(27 reference statements)
17
375
0
Order By: Relevance
“…This method, which accounts for the number of CpG sites and exposures tested, has been widely used in similar studies. [31][32][33] As a result, the adjusted level of significance in the current study was P-value D 9.4£ 10 ¡9 , i.e., 0.05 / (484,613£ 11). After identifying significant CpGs, we further checked whether they were non-unimodal in the dip test, 34 were cross-reactive, 35 or were located within 10 bases of SNPs relevant to European populations.…”
Section: Resultsmentioning
confidence: 63%
See 1 more Smart Citation
“…This method, which accounts for the number of CpG sites and exposures tested, has been widely used in similar studies. [31][32][33] As a result, the adjusted level of significance in the current study was P-value D 9.4£ 10 ¡9 , i.e., 0.05 / (484,613£ 11). After identifying significant CpGs, we further checked whether they were non-unimodal in the dip test, 34 were cross-reactive, 35 or were located within 10 bases of SNPs relevant to European populations.…”
Section: Resultsmentioning
confidence: 63%
“…42,43 SLFN11, a member of the SLFN family, potently and specifically abrogates the production of retroviruses, e.g., human immunodeficiency virus (HIV-1). 33 Using cells with endogenously high and low SLFN11 expression and siRNA-mediated silencing, Zoppoli et al 44 found that SLFN11 causally determines cell death and cell cycle arrest in response to DNA-damaging agents in cancer cells from different tissues of origin. SLFN11 cg10911913 is located in a region whose function is promoter associated.…”
Section: Discussionmentioning
confidence: 99%
“…Expressing vpx together with HIV-1 has been demonstrated to increase viral production extensively. The results from Li et al [1] add new evidence of an ISG, namely SLFN11, that controls HIV replication. Interestingly, the major function of SLFN11 is proposed to down-modulate HIV-1 mRNA translation.…”
Section: Human Immunodeficiency Virus Type 1 (Hiv-1) Is the Cause Ofmentioning
confidence: 88%
“…Subsequently, the cell produces spliced viral mRNAs that are transcribed into viral proteins using the host machinery. In a recent paper published in Nature, Li et al [1] describe schlafen (SLFN) 11 as a restriction factor for HIV, acting by regulating viral protein synthesis (Figure 1). Expression of SLFN genes was found to be induced by RNA, DNA, and type I interferon (IFN), hence classifying the SLFN proteins as interferon-stimulated genes (ISGs).…”
Section: Human Immunodeficiency Virus Type 1 (Hiv-1) Is the Cause Ofmentioning
confidence: 99%
See 1 more Smart Citation